Heart Rate-based Lactate Minimum Test in Running and Cycling - Perret, Claudio; Hartmann, Kathrin (International Journal of Sports Medicine, 2021)
The heart rate-based lactate minimum test is a highly reproducible exercise test. However, the relation between lactate minimum determined by this test and maximal lactate steady state in running and cycling is still unclear. Twelve endurance-trained men performed this test in running and cycling. Exercise intensity at maximal lactate steady state was determined by performing several constant heart rate endurance tests for both exercise modes. Heart rate, power output, lactate concentration, oxygen uptake and rating of perceived exertion at lactate minimum, maximal lactate steady state and maximal performance were analysed. All parameters were significantly higher at maximal lactate steady state compared to lactate minimum for running and cycling. Significant correlations (p<0.05) between maximal lactate steady state and lactate minimum data were found. Peak heart rate and peak oxygen uptake were significantly higher for running versus cycling. Nevertheless, the exercise mode had no influence on relative (in percentage of maximal values) heart rate at lactate minimum (p=0.099) in contrast to relative power output (p=0.002). In conclusion, all measured parameters at lactate minimum were significantly lower but highly correlated with values at maximal lactate steady state in running and cycling, which allows to roughly estimate exercise intensity at maximal lactate steady state with one single exercise test.
Keywords: exercise testing; endurance sports; training; exercise physiology; training intensities